Computational fluid dynamics of helicopter engine exhaust outflow - Chan, Kenneth Mun Chew (2017)
This paper reviews the computational study of the flow of exhaust gases in a helicopter’s Lobed Mixer Ejector or simply, an exhaust tailpipe. This study was done to investigate the directional flow of these multi-species fluids, when mixed with the entrained ambient air introduced by the rotor downwash. On top of that, the paper will highlight the heat dissipation from the ejector’s outlet, due to the significant amount of energy produced by the turboshaft’s combustion process. ANSYS Fluent was used in this analysis by simulating the theoretical fluid flow with hypothetical flight condition parameters.